Strategi Pengembangan Industri kecil Lovyna Konveksi Kediri - Hayati, Fina Nur; Subagyo, Subagyo; Hakimah, Ema Nurzainul (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2021)
Internal and external analysis of the company is an important factor in determining the right strategy for business development. The purpose of this study is to analyze the strengths, weaknesses, opportunities and threats and determine the right strategy for Lovyna Convection Kediri. Sources of data were obtained by observation interviews, questionnaires, interviews and documentation. The data analysis technique used descriptive techniques, while checking the validity of the findings used triangulation, peer discussion and extension of participation. The results of this study indicate that the Lovyna Convection Kediri Company is in quadrant I by implementing an aggressive strategy. (2) The strategy used by the convection company Lovyna Convection Kediri is the SO strategy, namely Strengths (strengths) and Opportunities (opportunities), namely by increasing the amount of production, increasing and maintaining product quality, increasing human resources, making product innovations, promoting through social media, expand the marketing area and follow the times or trend models and provide promos or discounts to consumers in order to attract consumer interest. Keywords: Business Development Strategy, SWOT Analysis